Mortality, disease and associated antimicrobial use in commercial small-scale chicken flocks in the Mekong Delta of Vietnam - Carrique-Mas, J; Van, N; Cuong, N; Truong, B; Kiet, B; Thanh, P; Lon, N; Giao, V; Hien, V; Padungtod, P; Choisy, M; Setyawan, E; et al. (Elsevier, 2019)
Raising chickens in small-scale flocks following all-in-all-out management is common in the Mekong Delta of Vietnam. These flocks represent an intermediate category between backyard and intensive (industrial) farming systems. However, little is known about the occurrence and burden of disease and/or mortality in such flocks, and their potential association with antimicrobial usage (AMU). We investigated mortality, disease and weekly antimicrobial use (AMU) in 124 cycles of meat chicken flocks raised in 88 farms in the Mekong Delta of Vietnam (with a median cycle duration of 18 weeks [inter-quartile range IQR 17–20]). We visited each farm 4 times per cycle to review data collected weekly by the farmers on clinical signs, mortality, and AMU. The overall probability of disease and AMU were 0.31 (95% CI 0.29–0.32) and 0.26 (95% CI 0.24–0.28), respectively. The average weekly incidence of mortality was 2.6 (95% CI 2.2–3.0) per 100 birds. Both the probabilities of a flock experiencing disease and mortality, as well as of using antimicrobials decreased with the flock's age. However, mortality peaked at the 5–10 week period. The only significant explanatory factors associated with presence of disease was the stage of production ≥5 weeks (protective) (OR ≤ 0.51). Factors independently associated with AMU (p < 0.05) were: (1) Number of chickens (log) (OR=1.46), (2) Stage of production ≥5 weeks (OR≤0.67) (protective), (3) Cao Lanh district (OR=2.23), (4) Density of veterinary drug shops at commune level (log) (OR=1.58), and (5) Disease in flocks (OR=1.80). Factors independently associated with overall increased weekly incidence of mortality (p < 0.05) were: (1) High level of education attainment (secondary education or higher) (Hazard rate Ratio [HR]=1.70), (2) number of chickens (log) (HR=1.39), and (3) Stage of production >5 weeks (HR≤2.14). In flocks reporting disease, AMU significantly reduced the incidence of mortality (HR=0.90). These results confirm an exceptionally high mortality in chicken flocks in the area, jeopardizing the profitability and sustainability of these small-scale farming systems. The data also suggest an association between nearby access to antimicrobials and AMU, and a high correlation of AMU over consecutive cycles. The atomized farming landscape of the Mekong Delta, the high incidence of disease and mortality, and the unrestricted and easy access to antimicrobials present major challenges to the implementation of policies aimed at AMU reductions.